Implementasi Finite State Automata pada Mesin Abstrak DFA dan NFA Berbasis Android - Dimas Dandy Aryarajendra Suprapto; Fauziah Fauziah (Universitas Indraprasta PGRI Jakarta, 2020)
FSA abstract machine (Finite State Automata) is a machine that is only seen from logic and processes and can use various programming languages to make it. The FSA Abstract Engine is accepting and rejecting an input. FSA is divided into two namely, DFA (Deterministic Finite Automata) and NFA (Non-deterministic Finite Automata). This paper discusses the use of the FSA algorithm to create DFA and NFA abstract machines based on Android. By using an android-based FSA abstract engine application the user can determine the input results of the automata process accepted or rejected easily and accurately without having to do manual calculations.